PENGARUH FREKUENSI PEMBERIAN PAKAN PADA KONDISI GELAP TERHADAP PERTUMBUHAN DAN SINTASAN BENIH IKAN LELE DUMBO (Clarias gariepinus) - Reza Alnanda; Yunasfi Djayus; Riri Ezraneti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The African catfish (Clarias gariepinus) is nocturnal, that is active at night or more like to dark place. The fry of catfish also requires high feeding frequency because the stomach is still small as a straight tube. This research was conducted to observe the effect of feeding frequency in dark condition to growth rate, survival rate and feeding efficiency of African catfish fry (C. gariepinus). The research was held on hatchery UPT Budidaya Dinas Pertanian dan Kelautan Kota Medan. Fry of catfish (C. gariepinus) were used average body size 8 - 9 cm and body weight 5 - 8 g, total fry cath fish 120 fish with stocking density 10 fish/washbasin. Twelve washbasin (50 liter volume) were used with aeration system and covered with black HD plastic layer to make dark condition for 24 hours. The parameter observed was 28 day were : growth rate, survival rate, feeding efficiency and water quality. Experimental design used a completely randomized design (CRD) with 4 treatment and 3 replications and further test use Least Significant Difference (LSD). The treatment was feeding frequency at 3 (at 08.00, 16.00 and 24.00), 4 meals (at 08.00, 14.00, 20.00 and 02.00), 5 meals (at 08.00, 12.48, 17.36, 22.24 and 03.12) and 6 meals (at 08.00, 12.00, 16.00, 20.00, 24.00 and 04.00) times a day in dark condition. The results indicated that the feeding frequency significantly effect to the growth rate and feeding efficiency, but did not significantly effect to survival rate. Feeding frequency 6 times a day is the best daily growth rate and feeding efficiency at 4,90% and 94,90%. Feeding frequency 3 times a day the old daily growth rate and feeding efficiency at 2,44%. and 44,03%.Keywords : Clarias gariepinus, feeding frequency, dark condition, growth.